Sleep disturbance in women who undergo surgical menopause compared with women who experience natural menopause. Issue 4 (April 2019) - Cho, Na Young; Kim, Soriul; Nowakowski, Sara; Shin, Chol; Suh, Sooyeon
Abstract: Objective: Women who undergo surgical menopause (SM) experience a relatively more acute and precipitous drop of estrogen compared with women who experience natural menopause (NM). Few studies, however, have compared sleep quality in women who experience natural versus SM. Methods: Participants were 526 postmenopausal women (mean age 60.2 ± 7.64). All participants completed self-report questionnaires about insomnia symptoms, sleep-interfering behaviors, depression, sleep quality, and gynecological history. Analysis of covariance was conducted to compare women who experienced NM versus SM on sleep variables. Logistic regression analysis was used to determine whether NM or SM groups predicted insomnia status. Regression-based moderation analysis was conducted to explore the moderating effect of type of menopause on the relationship between sleep-interfering behaviors and insomnia symptoms. Results: Among the sample, 81.6% ( n = 429) reported going through NM and 18.4% ( n = 97) reported going through SM. The SM group was significantly younger by 7.2 years ( P < 0.001). Women in the SM group reported significantly worse sleep quality ( P = 0.007), especially for sleep duration ( P = 0.001) and habitual sleep efficiency ( P = 0.010) compared with women in the NM group. Regression analysis indicated that individuals in the SM group were 2.131 (95% CI 1.055-4.303) times more likely to have insomnia compared with the NM group ( P = 0.027). In addition, women in the SM group who displayed more sleep-interfering behaviors also had a higher severity of insomnia symptoms compared with women who experience NM ( ß = 0.26, P = 0.03). Conclusions: Menopause can be both physically and psychologically challenging, but women who undergo SM experience worse sleep quality compared with women who experience NM, and may benefit from behavioral interventions.